2015
DOI: 10.5296/ijafr.v5i2.8035
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Perspectives on Corporate Social Responsibility Disclosure: A Critical Review

Abstract: This study provides an extensive critical review of the theoretical perspectives applied on corporate social responsibility (CSR) disclosure literature. From a CSR standpoint we review and discuss, in detail, legitimacy theory, stakeholder theory, social contract theory, and signalling theory to identify the situations that suit each of these perspectives. The findings show that there is no universal theory applicable on corporate social responsibility disclosure for all situations or societies. While legitima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 64 publications
4
100
0
12
Order By: Relevance
“…Deegan and Unerman (2011) in Omran and Ramdhony (2015) explained that the legitimacy theory relied on the notion that there was a "social contract" between an organization and the society in which it operated. The legitimacy theory uses motivation to get the endorsement from the community as said by Laan (2009) in Tarigan and Semuel (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Deegan and Unerman (2011) in Omran and Ramdhony (2015) explained that the legitimacy theory relied on the notion that there was a "social contract" between an organization and the society in which it operated. The legitimacy theory uses motivation to get the endorsement from the community as said by Laan (2009) in Tarigan and Semuel (2014).…”
Section: Introductionmentioning
confidence: 99%
“…To znači da organizacije trebaju poštivati mišljenja drugih dionika te nastojati graditi intersubjektivno razumijevanje i jasno definirati pravila igre (Habermas, 1979). Nadalje, u istraživanjima društveno odgovornog poslovanja koristi se i teorija legitimiteta kako bi se objasnilo zašto se poslovni subjekti odlučuju objaviti podatke o ekološkim i društvenim aspektima svojega poslovanja (Omran, 2015). Prema ovoj teoriji, poslovni subjekti trebaju djelovati unutar granica onoga što društvo identificira kao društveno prihvatljivo ponašanje.…”
Section: Corporate Social Responsibility In the Accommodation Sectorunclassified
“…Istraživanje je pokazalo da popularnije kući-ce ulažu veće napore u društveno odgovorno poslovanje i izvještavanje o njima nego one manje popularne. Tu je činjenicu moguće objasniti korištenjem teorije legitimnosti (Omran, 2015), pošto su popularnije kućice istovremeno i vidljivije i nalaze se pod većim pritiskom dionika da ispune društvene norme i očekivanja. Usto, posvećenost koju kućice pokazuju prema problemima zaštite okoliša i uključivanju u zajednicu (dvije najpopularnije teme) predstavljaju neformalno nastojanje za osiguranjem dopuštenja za nastavak djelo-vanja u svojoj zajednici.…”
Section: Rasprava I Zaključakunclassified
See 1 more Smart Citation
“…Review of the extent literature revealed that research in CSR were mainly concerned with CSR disclosures [3,7,8], corporate governance and strategic management [9,10], and the emerging political CSR [2,11]. Debates on CSR revolved around what theories are most suitable for companies to justify the basis of their CSR activities.…”
Section: Csr and Social Protectionmentioning
confidence: 99%